2007
DOI: 10.1186/1471-2164-8-125
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of Arabidopsis heat shock proteins and transcription factors reveals extensive overlap between heat and non-heat stress response pathways

Abstract: Background: The heat shock response of Arabidopsis thaliana is dependent upon a complex regulatory network involving twenty-one known transcription factors and four heat shock protein families. It is known that heat shock proteins (Hsps) and transcription factors (Hsfs) are involved in cellular response to various forms of stress besides heat. However, the role of Hsps and Hsfs under cold and non-thermal stress conditions is not well understood, and it is unclear which types of stress interact least and most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
402
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(431 citation statements)
references
References 78 publications
22
402
1
6
Order By: Relevance
“…the putative importance of their ATP-independent role in stabilizing proteins and membranes undergoing conformational disruption (Swindell et al, 2007). This ATP-independent function may be particularly important under anoxic conditions, since it reduces the energy-dependent de novo protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the putative importance of their ATP-independent role in stabilizing proteins and membranes undergoing conformational disruption (Swindell et al, 2007). This ATP-independent function may be particularly important under anoxic conditions, since it reduces the energy-dependent de novo protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…HSP production under stress conditions is the most important cellular response, preventing protein aggregation, denaturation, misfolding, and degradation (Hartl, 1996;Hofmann and Feder, 1999;Swindell et al, 2007;Liberek et al, 2008), and their importance in all living organisms, including plants, has been assessed under several different stress conditions potentially threatening cellular homeostasis and leading to protein dysfunction (Vierling, 1991;Hofmann and Feder, 1999;Koh, 2002;Swindell et al, 2007;Timperio et al, 2008). The heat shock response is primarily regulated at the transcriptional level by Hsfs.…”
mentioning
confidence: 99%
“…Nevertheless, a general pattern appears to be preserved in highly expressed genes, and the prevalence of CT-rich regions is more prominent in the two Thellungiella species compared with Arabidopsis. Arabidopsis heat shock protein 70 (AT3G09440) is known to be highly expressed under abiotic stress, including salt stress, both in Arabidopsis and T. salsuginea (Taji et al, 2004;Swindell et al, 2007). There is a pyrimidine-rich region close to the ATG initiation codon in the putative homologs of Thellungiella 5# UTR sequences (Supplemental Fig.…”
Section: Differences Between the Thellungiella Species And Arabidopsismentioning
confidence: 99%
“…Genome-wide analysis has shown that rice and Arabidopsis contain 26 and 21 Hsf genes, respectively (Mittal et al 2009;Swindell et al 2007). Binding specificities of plant Hsfs to different Hsp promoters have not been much analyzed.…”
Section: Noted That the Induced Response To Hs Is Lost If The Canonicmentioning
confidence: 99%